2004
DOI: 10.1002/art.20410
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the use and effect of assistive devices in patients with early rheumatoid arthritis: A two‐year followup of women and men

Abstract: Objective. To identify activity limitation in early rheumatoid arthritis (RA) to detect patients needing assistive devices. To evaluate the effects of assistive devices. Methods. A multicenter cohort of 284 early RA patients was examined using the Evaluation of Daily Activity Questionnaire 12 and 24 months after diagnosis.Results. The extent of activity limitation was stable over time for both women and men. Most limitations concerned eating and drinking. Women reported more difficulties than did men. The use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
1
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 22 publications
0
32
1
9
Order By: Relevance
“…Usage rates as reported in the present study are hard to compare with those of other studies concerning assistive devices in general [2,3,7,12], mainly because different definitions of usage have been used. None of the previous studies assessed the absolute frequency of usage as employed in the present study.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Usage rates as reported in the present study are hard to compare with those of other studies concerning assistive devices in general [2,3,7,12], mainly because different definitions of usage have been used. None of the previous studies assessed the absolute frequency of usage as employed in the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…In previous studies, proportions of patients possessing one or more assistive devices varied between 34% and 78% [3,[5][6][7]. This difference could probably be explained by variation in the number of assistive devices or groups of assistive devices that were taken into account [3,[5][6][7] or by differences among patient populations (age and disease duration [3,6]). Moreover, it has been demonstrated before that possession of assistive devices may vary along with country-related health care systems [5].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, when women and men with RA were subgrouped together with regard to grip force, it became evident that poor outcome assessed by the HAQ and EDAQ was related to low grip force, but not to sex (or age) per se. The activity limitations seen 3 years after the diagnosis of RA were of approximately the same magnitude as those seen after 1 and 2 years in both women and men (5). Several investigators, using the HAQ, have reported more pronounced activity limitations in women than men (2,4,(13)(14)(15)18,35), and this finding, together with a majority of other self-reported outcome measures, has …”
Section: Discussionmentioning
confidence: 63%
“…However, early in the disease course, the inflammatory process leads to a multitude of functional limitations (1)(2)(3)(4)(5). Several studies have also shown that RA is associated with a shortened life span, mainly due to coronary vascular disease (6 -8).…”
Section: Introductionmentioning
confidence: 99%